What Is The Prevalence Of Methicillin-Resistant Staphylococcus Au- Reus (MRSA) In Intensive Care Units Across Urban Hospitals ? : A Systematic Review - Gabriella Selara Pangarepo; Fenny (The International Journal of Medical Science and Health Research, 2025)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) remains a significant pathogen in healthcare settings, particularly in intensive care units (ICUs) where patients are highly vulnerable due to compromised immune systems and invasive procedures. The prevalence of MRSA in ICUs shows wide variation, ranging from 0% to 98.4%, influenced by factors such as geographic location, ICU type, and screening Methods: This systematic review adhered strictly to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines to ensure methodological rigor. Results: Forty studies were included in this systematic review. The reported MRSA prevalence rates varied widely, ranging from 0% to 98.4%. Specific rates included 81.5% in one study and 1.2% for colonization in another, with infection rates as low as 0.212%. Temporal trends showed declining rates in some regions (e.g., 7.9% with a declining trend from 2014-2020), while others reported no significant long-term change. Factors impacting prevalence included ICU type, refugee status, patient age, and decolonization practices. Discussion: The considerable heterogeneity in reported MRSA prevalence highlights the influence of diverse settings, patient populations, and definitions of MRSA (colonization vs. infection). Data specific to urban hospitals were limited, with most studies lacking detailed urban/rural breakdowns. This complicates direct comparisons and limits the generalizability of findings to all urban ICUs. Conclusion: MRSA prevalence in urban ICUs is highly variable, influenced by various factors including ICU type and patient characteristics. Further research with standardized reporting and a clearer urban/rural distinction is needed to inform targeted infection control strategies.